Enhancing Students’ Speaking Fluency Through Roleplaying Segmented Scenes from Inside Out 2: A Descriptive Qualitative Study - Riska Dwi Apriyani; Sam Hermansyah; Isumarni; Syamsu T (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
Speaking fluency remains a persistent challenge for EFL learners in Indonesia, where students frequently exhibit limited oral proficiency due to insufficient practice opportunities, speaking anxiety, and traditional teaching methods. This descriptive qualitative study explores the implementation of role-playing segmented scenes from the Pixar animated film Inside Out 2 as an innovative strategy to enhance senior high school students’ English speaking fluency. The research was conducted with 20 students from class X-5 at SMAN 6 Sidrap, South Sulawesi, Indonesia. Ten students were purposively selected as key informants. Data were collected through pre- and post-intervention speaking fluency tests, semi-structured interviews, and classroom documentation. Fluency was assessed using the indicators of total words attempted (TWA), total speaking time (TST), filled speaking time (FST), and total words delivered (TWD). These quantitative indicators were converted into disfluency percentage, initial speaking rate (ISR), and effective speaking rate (ESR), while qualitative data were analyzed using the Miles and Huberman model. The findings demonstrate that role-playing segmented scenes from Inside Out 2 effectively improved students’ speaking fluency. Post-intervention results showed increased speaking rates, reduced pauses and hesitations, and greater confidence and active participation. Students expressed highly positive responses, highlighting increased motivation, reduced anxiety, and a more engaging learning atmosphere through this context-rich, media-based activity. The study underscores the pedagogical value of integrating popular animated films into role-play activities as a practical and motivating approach to developing oral communication skills in EFL classrooms.